Peningkatan Daya Saing Dan Pasar Usaha Peyek 'Cinta Rasa' Di Kelurahan Karang, Semanding, Tuban: Upaya Meningkatkan Penjualan Pada Sektor Usaha Kecil Mikro - Hariyanti Hariyanti; Dede Mariyani (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This research aims to increase sales of the "Cinta Rasa" project business through the implementation of Mandiri KKN which meets the established principles. Through analysis of local economic conditions, it was found that more than 50% of food sector business actors in Tuban Regency do not yet have halal certification, which has become a mandatory requirement following Law Number 33 of 2014. This research includes the stages of preparation, implementation, evaluation, reporting, and follow-up to Mandiri KKN. It is hoped that Mandiri KKN will be able to provide students with knowledge, skills and awareness of social life, as well as encourage innovation in the field of entrepreneurship. The focus of this research is increasing sales of the "Cinta Rasa" dent business through the implementation of halal certification, thus providing certainty of product halal status which increases consumer confidence and sales potential.